2017
DOI: 10.3847/1538-4357/834/2/191
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Nuclear Outflow of the Milky Way: Studying the Kinematics and Spatial Extent of the Northern Fermi Bubble

Abstract: We report new observations from a systematic, spectroscopic, ultraviolet absorption-line survey that maps the spatial and kinematic properties of the high velocity gas in the Galactic Center (GC) region. We examine the hypothesis that this gas traces the biconical nuclear outflow. We use an ultraviolet spectra of 47 background QSOs and halo stars projected inside and outside

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
126
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(149 citation statements)
references
References 91 publications
(128 reference statements)
22
126
1
Order By: Relevance
“…The C II observations for LS 4825 are consistent with the outflow velocity versus galactic latitude trend established by the five lines of sight through the northern Fermi Bubble displayed in Figure 3 of Bordoloi et al (2017).…”
Section: The Kinematical Signature Of An Outflow In Multiple Gas Phasessupporting
confidence: 81%
See 1 more Smart Citation
“…The C II observations for LS 4825 are consistent with the outflow velocity versus galactic latitude trend established by the five lines of sight through the northern Fermi Bubble displayed in Figure 3 of Bordoloi et al (2017).…”
Section: The Kinematical Signature Of An Outflow In Multiple Gas Phasessupporting
confidence: 81%
“…In a subsequent paper Bordoloi et al (2017) studied the UV absorption toward five lines of sight passing through the northern Fermi Bubble and found that all five exhibited blue shifted high velocity components while only 9 of 42 lines of sight outside the Fermi Bubble exhibited blue shifted high velocity components. The blue shifted Galactic standard of rest (GSR) velocities for the high velocity absorbers in directions inside the Fermi Bubble change from v GSR = -265 to -91 km s -1 from Galactic latitude b = 11° to b = 50°.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by cross-matching the R17 sample with the Fox et al (2014) catalog of Stream absorbers, which covers sightlines within 30 • of the 21 cm emission from the Stream, and then removing matched sightlines from the sample. We also remove several sightlines passing through the Fermi Bubbles (Bordoloi et al 2017;Karim et al 2018), since the HVCs in these directions are thought to trace a nuclear wind and so are distinct from the general HVC population.…”
Section: Derivation Of Hvc Mass and Mass Flow Ratementioning
confidence: 99%
“…Finally, the HVC mass flow rates presented here do not include (by design) the Magellanic Stream and Leading Arm or the Fermi Bubbles, since these structures are physically unrelated to the remaining HVC population. The Stream represents an a much larger inflow rate of ≈3-7 M yr −1 (Fox et al 2014, R17) and the Fermi Bubbles have an outflow rate of 0.2-0.3 M yr −1 in cool gas (Bordoloi et al 2017).…”
Section: Velocity Limit Ionization and Saturation Effectsmentioning
confidence: 99%
“…The canonical threshold surface density for driving galactic outflows, Σ SFR > 0.1 M yr −1 kpc −2 , is based on local starburst galaxies (Heckman 2002). However, both recent integral field spectroscopy results from local main sequence galaxies (Ho et al 2016) and evidence of galactic outflows within the Milky Way Fermi Bub- bles (Fox et al 2015;Bordoloi et al 2017) suggest that galaxies with lower Σ SFR values (Σ SFR ≈ 10 −3 − 10 −1.5 M yr −1 kpc −2 ) can drive outflows. The threshold surface density may evolve with redshift (Sharma et al 2016) and may also depend on the galaxy properties, especially the gas fraction (Newman et al 2012).…”
Section: 4mentioning
confidence: 99%